The Ministry of Religious Congregations to People Affected by the SARS-CoV-2 Coronavirus in Poland: Geographies of Care During the COVID-19 Pandemic - Mróz, Franciszek (Journal of religion and health, 2022)
The aim of this article is to analyze the empirical evidence collected in the form of in-depth interviews, observations, statistics and accounts concerning the assistance provided by female and male religious congregations in the fight against the effects of the COVID-19 pandemic in Poland during the first year after the outbreak (March 2020 to February 2021). The paper describes the nature of the assistance rendered by religious congregations to the sick, to those affected by the pandemic and to healthcare facilities during the spread of the SARS-CoV-2 coronavirus in Poland. Our findings reveal that the activities undertaken and the support provided by religious congregations in the fight against the COVID-19 pandemic in Poland have spanned many areas: medical assistance and nursing within the healthcare system, charitable work (including material, financial and welfare/housing aid), and pastoral, religious, educational, psychological, ecumenical, evangelization and missionary activities. The support provided by religious congregations as part of the coronavirus response efforts proved crucial and invaluable during the first weeks of the pandemic, that is in March and April 2020, when the healthcare system was faced with severe staff shortages.